Preparation method and application of ferromagnetic high-entropy alloy / carbon sphere composite material modified lithium metal negative electrode current collector
The metal lithium negative electrode current collector is modified by strong magnetic high entropy alloy/carbon ball composite, which solves the problem of insufficient stability and cycle life of lithium negative electrode, and achieves uniform deposition of lithium ions and high energy density and safety of the battery, which significantly improves the The performance of lithium metal batteries.
Patent Information
- Application Number
- CN202411263044.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The stability and cycle life of the lithium negative electrode in existing lithium metal batteries is insufficient, mainly due to the accumulation of "dead lithium" caused by the growth of lithium dendrites and volume changes, resulting in the risk of thermal runaway and short circuit of the battery, and the external magnetic field construction is complex and costly. It is difficult to achieve large-scale application.
The metal lithium negative electrode current collector is modified by using strong magnetic high entropy alloy/carbon ball composite material, and the uniform deposition of lithium ions is promoted through cocktail synergy and gradient absorption energy sites. The micromagnetic field eliminates the concentration gradient of the electrode-electrolyte interface to form a uniform lithium Distributed and efficient conductive network.
It significantly improves the stability and cycle life of the lithium negative electrode, extends the energy density and safety of metal lithium batteries, the Coulomb efficiency reaches 99.43%, and the cycle life exceeds 12,000 hours, reducing the complexity and cost of experiments.
Smart Images

Figure CN119153673A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a metal lithium negative electrode current collector. Background Art
[0002] Judging from market feedback, short driving range is still a pain point that electric vehicles need to solve urgently. The main reason is that the energy density of lithium-ion batteries, the "heart" of electric vehicles, is low (150-300Wh / kg). Therefore, it is urgent to develop secondary power batteries with high energy density, safety and reliability. High energy density secondary battery systems require the use of positive and negative electrodes with high energy density. Metal lithium has a high theoretical specific capacity (3860mAhg -1 ), low electrode potential (-3.04V vs. standard hydrogen electrode), etc., and is recognized as an ideal negative electrode material for realizing high energy density battery systems. However, due to the uncontrollable growth of lithium dendrites and the huge volume change of the host-free lithium negative electrode, "dead lithium" accumulates rapidly, and eventually leads to the pulverization and failure of the metal lithium negative electrode. In addition, lithium negative electrodes will produce lithium dendrites during the cycle process, penetrate the diaphragm, cause short circuits, and increase the risk of thermal runaway of the battery. To address this problem, researchers have applied strategies such as lithium-philic current collectors, artificial solid electrolyte interface (SEI) membranes, all-solid / quasi-solid electrolytes, modified SEI membranes, and conductive three-dimensional skeletons to protect the metal lithium negative electrode, significantly improving the cycle performance of lithium metal batteries. However, the currently reported schemes still cannot make the lithium negative electrode exhibit satisfactory stability under the practical conditions of low negative electrode area capacity / positive electrode area capacity (N / P) ratio, lean solution, and high rate.
[0003] In order to further improve the stability of the lithium negative electrode, it is extremely important to ensure the uniform and dense deposition / stripping of lithium. The key is to eliminate the concentration gradient of lithium ions at the electrode-electrolyte interface and avoid the appearance of local hot spots. At the same time, ensure the uniform and dense nucleation of lithium ions. In recent years, many studies have reported that the use of magnetic fields as a non-contact energy transfer method can effectively improve the electrochemical performance of lithium metal batteries by relying on the influence of magnetic force, magnetization intensity, magnetohydrodynamics and spin effects. However, the construction of an external magnetic field will complicate the experimental process, greatly increase the experimental cost, and make it difficult to achieve large-scale application. Therefore, constructing a micromagnetic field in the current collector / lithium negative electrode host material is the focus and hot spot of current research, and it is also one of the strategies with the most research value and application prospects. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a preparation method and application of a metal lithium negative electrode current collector modified by a ferromagnetic high entropy alloy / carbon ball composite material.
[0005] A method for preparing a metal lithium negative electrode current collector modified by a ferromagnetic high entropy alloy / carbon ball composite material is specifically completed by the following steps:
[0006] 1. Preparation of hollow carbon spheres:
[0007] ①, anhydrous ethanol, deionized water and ammonia water are mixed, and stirred at room temperature for a period of time to obtain a mixed solution I; tetraethyl orthosilicate is added dropwise to the mixed solution I, and then resorcinol solution and formaldehyde solution are added, and stirred at room temperature for a period of time to obtain a precursor solution;
[0008] ②, transfer the precursor solution to the reaction kettle, and then carry out hydrothermal reaction at 100℃~200℃ for a period of time, and naturally cool to room temperature to obtain reaction product I; centrifuge and wash the reaction product I, and dry it to obtain SiO 2 @Phenolic resin beads;
[0009] ③. Under the protection of nitrogen atmosphere, SiO 2 @The phenolic resin pellets are heated to the carbonization temperature and carbonized at the carbonization temperature for a period of time to obtain the reaction product II; the reaction product II is immersed in a NaOH solution for a period of time, then washed with deionized water until neutral, and dried to obtain hollow carbon spheres;
[0010] 2. Preparation of high magnetic high entropy alloy / carbon ball composite materials:
[0011] ①. Weigh 2 to 5 different metal salts in equal molar ratio and add them to deionized water. Then add FeCl in equal molar ratio to one metal salt. 2 ·4H 2 O、CoCl 2 6H 2 O and NiCl 2 6H 2 O, stirring evenly, and then ultrasonicating to form a uniform solution to obtain a mixed solution II;
[0012] ②, immerse the hollow carbon spheres in the mixed solution II, stir for a period of time, and then use a rotary evaporator to dry the mixture to obtain the reaction product III; 2 and Ar mixed gas atmosphere protection and annealing at a temperature of 800°C to 1000°C for a period of time to obtain a high magnetic high entropy alloy / carbon ball composite material;
[0013] 3. Modification of metal lithium negative electrode current collector:
[0014] ①, adding high magnetic high entropy alloy / carbon ball composite material and polyvinylidene fluoride into N-methylpyrrolidone, ultrasonicating for a period of time to obtain a viscous slurry;
[0015] ②. Apply the viscous slurry on one surface of the double-sided copper foil, and then vacuum dry it to obtain a strong magnetic high entropy alloy / carbon ball composite material modified metal lithium negative electrode current collector.
[0016] A strong magnetic high entropy alloy / carbon ball composite material modified with a metallic lithium negative electrode current collector is used in lithium metal batteries.
[0017] Principle of the present invention:
[0018] Based on the serious problem of lithium dendrite growth in practical lithium negative electrode, the present invention uses high magnetic high entropy alloy / carbon ball composite material to modify the traditional lithium negative electrode current collector. The current collector has the following effects in inhibiting the growth of lithium dendrites: (1) The cocktail synergistic effect between different components in the high entropy alloy realizes multiple lithium ion transmission paths and abundant active sites; (2) The existence of high entropy effect makes the high entropy alloy have active sites with gradient absorption energy, which is conducive to selective binding of lithium ions, thereby providing a low barrier for uniform lithium nucleation; (3) Multiple transmission paths promote the diffusion behavior of lithium ions and uniform lithium deposition; (4) There are a large number of micromagnetic fields around the nano high entropy alloy. The magnetic vortex effect under the action of the magnetic field helps to eliminate the concentration gradient at the electrode-electrolyte interface and induce the uniform distribution of lithium ions; (5) The special structure of the composite carbon ball also helps to homogenize the distribution of the electric field on the surface of the current collector, avoiding the appearance of the "tip effect". Based on the above advantages, the strong magnetic high entropy alloy / carbon ball composite material modified with the metal lithium negative electrode current collector can enhance the uniformity of the deposition behavior of metal lithium, inhibit the formation of lithium dendrites, inhibit the consumption of electrolyte, extend the life of the metal lithium negative electrode, increase the energy density of the battery, and significantly improve its cycle life, stability and safety.
[0019] The present invention has the following beneficial effects:
[0020] 1. The ferromagnetic high entropy alloy / carbon ball composite material modified metal lithium negative electrode current collector obtained by the present invention has a unique three-dimensional structure. The continuous conductive network of the three-dimensional porous conductive skeleton has a high electroactive specific surface area, which can make the external current evenly distributed on the entire porous skeleton, reduce the effective current density, and thus homogenize the distribution of the electric field around the skeleton. The uniform electric field can homogenize the lithium ion mass transfer flow, which is conducive to the uniform deposition of lithium;
[0021] 2. The ferromagnetic high entropy alloy / carbon ball composite material modified lithium metal negative electrode current collector obtained by the present invention has a gradient binding energy with lithium ions, so that the ferromagnetic high entropy alloy / carbon ball composite material modified lithium metal negative electrode current collector has excellent lithium affinity, reduces the lithium nucleation energy barrier, and ensures uniform and dense nucleation of lithium;
[0022] 3. The surface of the metal lithium negative electrode current collector modified by the ferromagnetic high entropy alloy / carbon ball composite material obtained by the present invention has a large amount of micromagnetic field. Under the action of the Lorentz force, the lithium ions show a magnetic vortex effect, which helps to eliminate the concentration gradient at the electrode-electrolyte interface and induce the uniform distribution of lithium ions;
[0023] 4. The presence of a micromagnetic field on the surface of the metal lithium negative electrode current collector modified by the ferromagnetic high entropy alloy / carbon ball composite material obtained by the present invention can also induce lithium ions to deposit at the bottom of lithium dendrites, avoiding the occurrence of the tip effect;
[0024] 5. The application of the ferromagnetic high entropy alloy / carbon ball composite material obtained by the present invention to modify the metal lithium negative electrode current collector can make the coulomb efficiency of the lithium negative electrode reach 99.43%, and can stably cycle for more than 12000h. The soft pack battery using the ferromagnetic high entropy alloy / carbon ball composite material to modify the metal lithium negative electrode current collector composite lithium negative electrode can stably cycle 500 times, which is much higher than the battery using the conventional current collector;
[0025] 6. The preparation method of the ferromagnetic high entropy alloy / carbon ball composite material modified metal lithium negative electrode current collector of the present invention is simple and easy, and does not require complicated process flow and equipment. The preparation method of the present invention has been verified by multiple experiments and has strong reproducibility and stability, which can ensure the consistency of product quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The microscopic morphology of the high magnetic high entropy alloy / carbon ball composite material prepared in step 2 of Example 1, the left picture is a scanning electron microscope image, and the right picture is a transmission electron microscope image;
[0027] Figure 2 The distribution diagram of different metal elements in the high magnetic high entropy alloy / carbon ball composite material prepared in step 2 of Example 1;
[0028] Figure 3 To use multi-physics simulation software to simulate the movement trajectory and distribution of lithium ions around lithium dendrites in the absence of a magnetic field;
[0029] Figure 4 To use multi-physics simulation software to simulate the movement trajectory and distribution of lithium ions around lithium dendrites in the presence of a magnetic field;
[0030] Figure 5 To simulate the distribution of the electric field and lithium ion concentration field on the surface of the metal lithium negative electrode current collector modified by the ferromagnetic high entropy alloy / carbon ball composite material prepared in Example 1 using multi-physics field simulation software;
[0031] Figure 6 This is a coulomb efficiency test diagram of metal lithium deposition / stripping on a metal lithium negative electrode current collector modified with a ferromagnetic high entropy alloy / carbon ball composite material prepared in Example 1;
[0032] Figure 7 This is a test diagram of the cycle life of a lithium-lithium symmetric battery assembled with a composite lithium negative electrode modified with a metal lithium negative electrode current collector and a ferromagnetic high entropy alloy / carbon ball composite prepared in Example 1;
[0033] Figure 8 This is a test chart of the cycle life of a lithium metal soft-pack battery assembled with a composite lithium negative electrode modified with a metal lithium negative electrode current collector and a ferromagnetic high entropy alloy / carbon ball composite prepared in Example 1. DETAILED DESCRIPTION
[0034] Specific implementation method 1: This implementation method is a method for preparing a metal lithium negative electrode current collector modified by a ferromagnetic high entropy alloy / carbon ball composite material, which is specifically completed by the following steps:
[0035] 1. Preparation of hollow carbon spheres:
[0036] ①, anhydrous ethanol, deionized water and ammonia water are mixed, and stirred at room temperature for a period of time to obtain a mixed solution I; tetraethyl orthosilicate is added dropwise to the mixed solution I, and then resorcinol solution and formaldehyde solution are added, and stirred at room temperature for a period of time to obtain a precursor solution;
[0037] ②, transfer the precursor solution to the reaction kettle, and then carry out hydrothermal reaction at 100℃~200℃ for a period of time, and naturally cool to room temperature to obtain reaction product I; centrifuge and wash the reaction product I, and dry it to obtain SiO 2 @Phenolic resin beads;
[0038] ③. Under the protection of nitrogen atmosphere, SiO 2 @The phenolic resin pellets are heated to the carbonization temperature and carbonized at the carbonization temperature for a period of time to obtain the reaction product II; the reaction product II is immersed in a NaOH solution for a period of time, then washed with deionized water until neutral, and dried to obtain hollow carbon spheres;
[0039] 2. Preparation of high magnetic high entropy alloy / carbon ball composite materials:
[0040] ①. Weigh 2 to 5 different metal salts in equal molar ratio and add them to deionized water. Then add FeCl in equal molar ratio to one metal salt. 2 ·4H 2 O、CoCl 2 6H 2 O and NiCl 2 6H 2 O, stirring evenly, and then ultrasonicating to form a uniform solution to obtain a mixed solution II;
[0041] ②, immerse the hollow carbon spheres in the mixed solution II, stir for a period of time, and then use a rotary evaporator to dry the mixture to obtain the reaction product III; 2 and Ar mixed gas atmosphere protection and annealing at a temperature of 800°C to 1000°C for a period of time to obtain a high magnetic high entropy alloy / carbon ball composite material;
[0042] 3. Modification of metal lithium negative electrode current collector:
[0043] ①, adding high magnetic high entropy alloy / carbon ball composite material and polyvinylidene fluoride into N-methylpyrrolidone, ultrasonicating for a period of time to obtain a viscous slurry;
[0044] ②. Apply the viscous slurry on one surface of the double-sided copper foil, and then vacuum dry it to obtain a strong magnetic high entropy alloy / carbon ball composite material modified metal lithium negative electrode current collector.
[0045] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that the volume ratio of anhydrous ethanol, deionized water and ammonia water in the mixed solution I described in step 1① is (65-75): (5-15): (25-40); the volume ratio of tetraethyl orthosilicate to the mixed solution I described in step 1① is (1-5): (110-120). The other steps are the same as those in specific embodiment 1.
[0046] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the mass ratio of the resorcinol solution described in step one ① to the mixed solution I is (0.1g-0.5g):(110mL-120mL); the mass fraction of the resorcinol solution is 90%-98%; the volume ratio of the formaldehyde solution described in step one ① to the mixed solution I is (0.1-1):(110-120); the mass fraction of the formaldehyde solution is 93%-98%. The other steps are the same as specific implementation method one or two.
[0047] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: in step 1①, anhydrous ethanol, deionized water and ammonia water are mixed and stirred at room temperature for 20 min to 40 min to obtain a mixed solution I; tetraethyl orthosilicate is added dropwise to the mixed solution I, and then resorcinol solution and formaldehyde solution are added, and then stirred at room temperature for 20 h to 26 h to obtain a precursor solution. The other steps are the same as those of specific embodiments 1 to 3.
[0048] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the time of the hydrothermal reaction described in step 1 ② is 2h to 4h; in step 1 ②, the reaction product I is centrifugally washed 3 to 5 times with deionized water, the speed of the centrifugal washing is 5000r / min to 8000r / min, and the time of each centrifugal washing is 5min to 10min; in step 1 ②, the reaction product I is placed in a vacuum drying oven at a temperature of 60℃ to 80℃ for 10h to 12h. The other steps are the same as those of specific embodiments 1 to 4.
[0049] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the carbonization temperature in step 1 ③ is 800 ℃ to 1000 ℃; the carbonization time in step 1 ③ is 1h to 3h; the concentration of the NaOH solution in step 1 ③ is 2.5mol / L to 3mol / L; the time for immersing the reaction product II in the NaOH solution in step 1 ③ is 4 days to 6 days; the drying temperature in step 1 ③ is 50 ℃ to 80 ℃, and the drying time is 12h to 16h. The other steps are the same as those in specific embodiments 1 to 5.
[0050] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the metal salt described in step 2① is H 2 PtCl 6 6H 2 O, CuCl 2 ·2H 2 O、WCl 4 ·4H 2 O、CrCl 2 ·2H 2 O、MnCl 2 ·3H 2 O、ZnCl 2 6H 2 O or CuCl 2 ·2H 2 O; the total molar number of the metal salt in the mixed solution II described in step 2① is 1×10 - 4 The other steps are the same as those in Specific Embodiments 1 to 6.
[0051] Specific embodiment 8: The difference between this embodiment and specific embodiments 1 to 7 is that the volume ratio of the mass of the hollow carbon spheres described in step 2② to the mixed solution II is (0.1g to 0.3g): (1mL to 4mL); the H 2 H in a mixed gas of Ar 2 The volume ratio of Ar to Ar is 5:1; the annealing time in step 2② is 2h to 3h; in step 2②, the hollow carbon sphere is immersed in the mixed solution II, stirred for 8h to 12h, and then the mixture is dried at 60℃ to 80℃ using a rotary evaporator to obtain a reaction product III. The other steps are the same as those in specific embodiments 1 to 7.
[0052] Specific embodiment nine: This embodiment differs from specific embodiments one to eight in that: the mass ratio of the high magnetic high entropy alloy / carbon ball composite material to polyvinylidene fluoride described in step three ① is 90:(1 to 10); the mass ratio of the high magnetic high entropy alloy / carbon ball composite material described in step three ① to the volume ratio of N-methylpyrrolidone is 90mg:(500μL to 1000μL); the ultrasonic time described in step three ① is 20min to 40min; the thickness of the viscous slurry coated on the copper foil described in step three ② is 5μm to 10μm; the vacuum drying temperature described in step three ② is 60℃ to 80℃, and the vacuum drying time is 10h to 12h. The other steps are the same as specific embodiments one to eight.
[0053] Specific embodiment ten: This embodiment is an application of a metal lithium negative electrode current collector modified by a ferromagnetic high entropy alloy / carbon ball composite material in a lithium metal battery.
[0054] The following examples are used to verify the beneficial effects of the present invention:
[0055] Example 1: A method for preparing a metal lithium negative electrode current collector modified by a ferromagnetic high entropy alloy / carbon ball composite material, which is specifically completed by the following steps:
[0056] 1. Preparation of hollow carbon spheres:
[0057] ①, anhydrous ethanol, deionized water and ammonia water were mixed, and stirred at room temperature for 30 minutes to obtain a mixed solution I; tetraethyl orthosilicate was added dropwise to the mixed solution I, and then resorcinol solution and formaldehyde solution were added, and then stirred at room temperature for 24 hours to obtain a precursor solution;
[0058] The volume ratio of anhydrous ethanol, deionized water and ammonia water in the mixed solution I described in step 1① is 70:10:33;
[0059] The volume ratio of tetraethyl orthosilicate described in step 1① to mixed solution I is 1.5:113;
[0060] The mass ratio of the resorcinol solution described in step 1① to the volume ratio of the mixed solution I is 0.2g:113mL; the mass fraction of the resorcinol solution is 95%;
[0061] The volume ratio of the formaldehyde solution described in step 1① to the mixed solution I is 0.8:110; the mass fraction of the formaldehyde solution is 95%;
[0062] ②, transfer the precursor solution to the reactor, and then perform hydrothermal reaction at 100 ° C for 2 hours, and naturally cool to room temperature to obtain reaction product I; centrifuge and wash the reaction product I three times with deionized water, and then dry it at 60 ° C for 12 hours to obtain SiO 2@Phenolic resin beads;
[0063] The speed of centrifugal washing in step 1② is 5000r / min, and the time of each centrifugal washing is 5min;
[0064] ③. Under the protection of nitrogen atmosphere, SiO 2 @The phenolic resin beads were heated to 1000°C and carbonized at 1000°C for 2 hours to obtain reaction product II; the reaction product II was immersed in a 2.8 mol / L NaOH solution for 5 days, then washed with deionized water until neutral, and then dried at 60°C for 16 hours to obtain hollow carbon spheres;
[0065] 2. Preparation of high magnetic high entropy alloy / carbon ball composite materials:
[0066] ①, weigh FeCl in equal molar ratio 2 ·4H 2 O、CoCl 2 6H 2 O、NiCl 2 6H 2 O, H 2 PtCl 6 -6H 2 O and CuCl 2 -2H 2 O was added into deionized water, stirred evenly, and then ultrasonicated for 60 min at an ultrasonic power of 500 W to form a uniform solution to obtain a mixed solution II;
[0067] FeCl in the mixed solution II described in step 2① 2 ·4H 2 O、CoCl 2 6H 2 O、NiCl 2 6H 2 O, H 2 PtCl 6 -6H 2 O and CuCl 2 -2H 2 The total number of moles of O is 1×10 -4 mol;
[0068] ②, immerse the hollow carbon spheres in the mixed solution II, stir for 2 hours, and then use a rotary evaporator to dry the mixture at 80°C for 12 hours to obtain the reaction product III; put the reaction product III into a tubular furnace at a temperature of 1000°C, and heat the reaction product III in H 2 Annealing was performed for 2 h under the protection of a mixed gas atmosphere of Ar to obtain a high magnetic high entropy alloy / carbon ball composite material;
[0069] The mass ratio of the hollow carbon spheres described in step 2② to the volume ratio of the mixed solution II is 0.1 g:4 mL;
[0070] H described in step 2② 2 H in a mixed gas of Ar 2 The volume ratio of Ar is 5:1;
[0071] The annealing temperature in step 2② is 1000°C;
[0072] 3. Modification of metal lithium negative electrode current collector:
[0073] ①, add 90 mg of high magnetic high entropy alloy / carbon ball composite material and 10 mg of polyvinylidene fluoride into 500 μL of N-methylpyrrolidone, and ultrasonicate for 30 min to obtain a viscous slurry;
[0074] ②, apply the viscous slurry on one surface of the smooth copper foil, and then vacuum dry it at 60°C for 12 hours to obtain a strong magnetic high entropy alloy / carbon ball composite material modified metal lithium negative electrode current collector;
[0075] The thickness of the viscous slurry coated on the surface of the copper foil in step 3② is 50 μm.
[0076] Figure 1 The microscopic morphology of the high magnetic high entropy alloy / carbon ball composite material prepared in step 2 of Example 1, the left picture is a scanning electron microscope image, and the right picture is a transmission electron microscope image;
[0077] Figure 1 It was proved that the material was a hollow sphere with a diameter of about 400nm, and the high entropy alloy was evenly distributed on the surface of the carbon sphere.
[0078] Figure 2 The distribution diagram of different metal elements in the high magnetic high entropy alloy / carbon ball composite material prepared in step 2 of Example 1;
[0079] Figure 2 The distribution of elements such as Pt, Cu, Fe, Co, and Ni on the surface of carbon spheres further proves that the high entropy alloy is evenly distributed on the surface of carbon spheres.
[0080] contrast Figure 3 and Figure 4 , it can be proved that in the presence of a magnetic field, the moving lithium ions will produce a sub-vortex effect, avoiding the generation of a tip effect and ensuring uniform deposition of lithium ions.
[0081] like Figure 5 As shown: the microstructure of the surface of the metal lithium negative electrode current collector modified by the ferromagnetic high entropy alloy / carbon ball composite material prepared in Example 1 can effectively make the electric field and lithium ion concentration field around the current collector uniform.
[0082] Application Example: In this example, the ferromagnetic high entropy alloy / carbon ball composite material modified lithium metal negative electrode current collector prepared in Example 1 is used as the current collector of the lithium metal electrode, and its performance is tested as follows:
[0083] The electrochemical tests were performed using the LAND CT3001A battery testing system produced by Wuhan Landian Electronics Co., Ltd.
[0084] 1. Assembly and testing of lithium-lithium symmetric batteries:
[0085] The composite lithium negative electrode is prepared by electrochemical deposition of the ferromagnetic high entropy alloy / carbon ball composite material prepared in Example 1 on a metal lithium negative electrode current collector, the ferromagnetic high entropy alloy / carbon ball composite material prepared in Example 1 modified with the metal lithium negative electrode current collector is used as the working electrode, the commercial metal lithium sheet is used as the counter electrode, and the ether electrolyte is used as the electrolyte (LiTFSI is dissolved in a mixed solution of DOL and DME with a volume ratio of 1:1, and LiNO is added 3 , to obtain an electrolyte; the concentration of LiTFSI in the electrolyte is 1 mol / L, LiNO 3 The mass fraction of 2wt%) was 2wt%), Celgard 2400 was used as the separator, and assembled into a CR-2032 button cell. -2 The deposition was carried out for 10 h at a current density of .
[0086] The battery was disassembled, the composite lithium anode was taken out, and the same three-dimensional composite lithium anode was used as the working electrode and the counter electrode at the same time. The ether electrolyte was used as the electrolyte (LiTFSI was dissolved in a mixed solution of DOL and DME with a volume ratio of 1:1, and LiNO was added 3 , to obtain an electrolyte; the concentration of LiTFSI in the electrolyte is 1 mol / L, LiNO 3 The mass fraction of 2wt%) was 2wt%), Celgard 2400 was used as the separator, and assembled into a CR-2032 button cell. -2 , capacity 1mAhcm -2 Constant current charge and discharge test was carried out under the conditions of
[0087] 2. Assembly and testing of lithium-current collector batteries:
[0088] In order to test the coulombic efficiency of metal lithium deposition / stripping on different current collectors, a metal lithium negative electrode current collector modified with a ferromagnetic high entropy alloy / carbon sphere composite was used as the working electrode, a metal lithium sheet was used as the counter electrode and reference electrode, and an ether electrolyte was used as the electrolyte (LiTFSI was dissolved in a mixed solution of DOL and DME with a volume ratio of 1:1, and LiNO was added). 3, to obtain an electrolyte; the concentration of LiTFSI in the electrolyte is 1 mol / L, LiNO 3 The mass fraction of 2wt%) was 2wt%), Celgard 2400 was used as the separator, and assembled into a CR-2032 button cell. -2 , capacity 1mAh cm -2 Constant current charge and discharge test was carried out under the conditions of
[0089] 3. Assembly and testing of lithium iron phosphate soft pack batteries:
[0090] The composite lithium negative electrode is prepared by electrodeposition of metallic lithium in the ferromagnetic high entropy alloy / carbon ball composite material modified metallic lithium negative electrode current collector prepared in Example 1, and the deposition capacity is 10 mAh cm -2 The commercial lithium iron phosphate electrode sheet was used as the positive electrode, and the loading amount of active material was 26 mg cm -2 Ether electrolyte was used as electrolyte (LiTFSI was dissolved in a mixed solution of DOL and DME with a volume ratio of 1:1, and LiNO 3 , to obtain an electrolyte; the concentration of LiTFSI in the electrolyte is 1 mol / L, LiNO 3 The mass fraction of 2wt%), Celgard 2400 as a separator, assembled into a soft pack battery, the electrolyte dosage is 2g / Ah. The assembled full battery was subjected to constant current charge and discharge test at a current density of 1C and a voltage window of 2.6-3.8V.
[0091] Comparative Example: A conventional commercial double-sided copper foil was used as the current collector and subjected to the same performance test.
[0092] Electrochemical performance:
[0093] like Figure 6 As shown, the coulombic efficiency of lithium deposition / stripping can be increased to 99.83% by modifying the metal lithium negative electrode current collector with the ferromagnetic high entropy alloy / carbon ball composite material prepared in Example 1. Figure 7 As shown, the lithium-lithium symmetric battery with a composite lithium negative electrode modified with a metal lithium negative electrode current collector and a composite lithium negative electrode prepared by using the ferromagnetic high entropy alloy / carbon ball composite material prepared in Example 1 can stably cycle for more than 17000 hours; Figure 8 As shown, the cycle life of the soft-pack battery (positive electrode active material is lithium iron phosphate) using the ferromagnetic high entropy alloy / carbon ball composite material prepared in Example 1 to modify the metal lithium negative electrode current collector composite lithium negative electrode is significantly improved compared with the use of conventional metal lithium negative electrode.
[0094] In summary, compared with the prior art, the present invention has the following advantages and outstanding effects: the present invention modifies the metal lithium negative electrode current collector with a strong magnetic high entropy alloy / carbon ball composite material, regulates the mass transfer behavior of lithium ions at the current collector-electrolyte interface, eliminates the lithium ion concentration gradient on the current collector surface, homogenizes the electric field and lithium ion concentration field around the current collector, and avoids the appearance of the tip effect. In addition, the "cocktail effect" of the high entropy alloy makes the current collector have a continuous lithium affinity strength, which can reduce the lithium nucleation energy barrier, the nucleation and growth behavior of lithium, inhibit the growth of lithium dendrites, alleviate the volume change of the metal lithium negative electrode during the cycle, improve the stability of the metal lithium negative electrode and significantly extend the cycle life and cycle capacity retention rate of the metal lithium battery.
Claims
1. A method for preparing a metal lithium negative electrode current collector modified by a ferromagnetic high entropy alloy / carbon ball composite material, characterized in that The preparation method is specifically completed according to the following steps:
1. Preparation of hollow carbon spheres: ①, anhydrous ethanol, deionized water and ammonia water are mixed, and stirred at room temperature for a period of time to obtain a mixed solution I; tetraethyl orthosilicate is added dropwise to the mixed solution I, and then resorcinol solution and formaldehyde solution are added, and stirred at room temperature for a period of time to obtain a precursor solution; ②, transfer the precursor solution to the reaction kettle, and then carry out hydrothermal reaction at 100℃~200℃ for a period of time, and naturally cool to room temperature to obtain reaction product I; The reaction product I is centrifuged, washed, and dried to obtain SiO2@phenolic resin pellets; ③. Under the protection of nitrogen atmosphere, the SiO2@phenolic resin pellets are heated to the carbonization temperature and carbonized at the carbonization temperature for a period of time to obtain the reaction product II; The reaction product II is immersed in a NaOH solution for a period of time, then washed with deionized water until neutral, and dried to obtain hollow carbon spheres; 2. Preparation of high magnetic high entropy alloy / carbon ball composite materials: ①, weigh 2 to 5 different metal salts in equal molar ratio and add them to deionized water, then add FeCl2·4H2O, CoCl2·6H2O and NiCl2·6H2O in equal molar ratio to one metal salt in turn, stir evenly, and then ultrasonicate to form a uniform solution to obtain mixed solution II; ②, immersing the hollow carbon spheres in the mixed solution II, stirring for a period of time, and then using a rotary evaporator to dry the mixture to obtain a reaction product III; annealing the reaction product III for a period of time under the protection of a mixed gas atmosphere of H2 and Ar at a temperature of 800°C to 1000°C to obtain a high magnetic high entropy alloy / carbon sphere composite material; 3. Modification of metal lithium negative electrode current collector: ①, adding high magnetic high entropy alloy / carbon ball composite material and polyvinylidene fluoride into N-methylpyrrolidone, ultrasonicating for a period of time to obtain a viscous slurry; ②. Apply the viscous slurry on one surface of the double-sided copper foil, and then vacuum dry it to obtain a strong magnetic high entropy alloy / carbon ball composite material modified metal lithium negative electrode current collector.
2. The method for preparing a ferromagnetic high entropy alloy / carbon ball composite material modified metal lithium negative electrode current collector according to claim 1, characterized in that The volume ratio of anhydrous ethanol, deionized water and ammonia water in the mixed solution I described in step 1① is (65-75):(5-15):(25-40); the volume ratio of tetraethyl orthosilicate described in step 1① to the mixed solution I is (1-5):(110-120).
3. The method for preparing a metal lithium negative electrode current collector modified by a ferromagnetic high entropy alloy / carbon ball composite material according to claim 1, characterized in that The mass ratio of the resorcinol solution described in step 1① to the volume ratio of the mixed solution I is (0.1g~0.5g):(110mL~120mL); the mass fraction of the resorcinol solution is 90%~98%; the volume ratio of the formaldehyde solution described in step 1① to the mixed solution I is (0.1~1):(110~120); the mass fraction of the formaldehyde solution is 93%~98%.
4. The method for preparing a metal lithium negative electrode current collector modified by a ferromagnetic high entropy alloy / carbon ball composite material according to claim 1, characterized in that In step 1①, anhydrous ethanol, deionized water and ammonia water are mixed, and stirred at room temperature for 20min to 40min to obtain a mixed solution I; tetraethyl orthosilicate is added dropwise to the mixed solution I, and then resorcinol solution and formaldehyde solution are added, and then stirred at room temperature for 20h to 26h to obtain a precursor solution.
5. The method for preparing a ferromagnetic high entropy alloy / carbon ball composite material modified metal lithium negative electrode current collector according to claim 1, characterized in that The time of the hydrothermal reaction described in step 1② is 2h~4h; in step 1②, the reaction product I is centrifuged and washed 3~5 times with deionized water, the speed of the centrifugal washing is 5000r / min~8000r / min, and the time of each centrifugal washing is 5min~10min; in step 1②, the reaction product I is placed in a vacuum drying oven at a temperature of 60℃~80℃ and dried for 10h~12h.
6. The method for preparing a ferromagnetic high entropy alloy / carbon ball composite material modified metal lithium negative electrode current collector according to claim 1, characterized in that The carbonization temperature described in step 1③ is 800℃~1000℃; the carbonization time described in step 1③ is 1h~3h; the concentration of the NaOH solution described in step 1③ is 2.5mol / L~3mol / L; the time for immersing the reaction product II in the NaOH solution in step 1③ is 4 days to 6 days; the drying temperature described in step 1③ is 50℃~80℃, and the drying time is 12h~16h.
7. The method for preparing a metal lithium negative electrode current collector modified by a ferromagnetic high entropy alloy / carbon ball composite material according to claim 1, characterized in that The metal salt described in step 2① is H2PtCl6·6H2O, CuCl2·2H2O, WCl4·4H2O, CrCl2·2H2O, MnCl2·3H2O, ZnCl2·6H2O or CuCl2·2H2O; The total molar number of metal salt in the mixed solution II described in step 2① is 1×10 -4 mol.
8. The method for preparing a metal lithium negative electrode current collector modified by a ferromagnetic high entropy alloy / carbon ball composite material according to claim 1, characterized in that The mass ratio of the hollow carbon spheres described in step 2② to the volume ratio of the mixed solution II is (0.1g~0.3g):(1mL~4mL); the volume ratio of H2 and Ar in the mixed gas of H2 and Ar described in step 2② is 5:1; the annealing time described in step 2② is 2h~3h; in step 2②, the hollow carbon spheres are immersed in the mixed solution II, stirred for 8h~12h, and then the mixture is dried at 60℃~80℃ using a rotary evaporator to obtain a reaction product III.
9. The method for preparing a metal lithium negative electrode current collector modified by a ferromagnetic high entropy alloy / carbon ball composite material according to claim 1, characterized in that The mass ratio of the high magnetic high entropy alloy / carbon ball composite material described in step 3① to polyvinylidene fluoride is 90:(1~10); the volume ratio of the high magnetic high entropy alloy / carbon ball composite material described in step 3① to N-methylpyrrolidone is 90mg:(500μL~1000μL); the ultrasonic time described in step 3① is 20min~40min; the thickness of the viscous slurry coated on the copper foil described in step 3② is 5μm~10μm; the vacuum drying temperature described in step 3② is 60℃~80℃, and the vacuum drying time is 10h~12h.
10. Application of a ferromagnetic high entropy alloy / carbon ball composite material modified with a metal lithium negative electrode current collector prepared by the preparation method according to claim 1, characterized in that A strong magnetic high entropy alloy / carbon ball composite material modified with a metallic lithium negative electrode current collector is used in lithium metal batteries.
Citation Information
Patent Citations
Preparation and application of liquid sodium-potassium alloy coated flexible hollow carbon paper electrode
CN113745464A
Preparation method and application of platinum-iron-cobalt-nickel-copper high-entropy alloy with gradient surface layer components
CN114985754A
Polymer / metal salt composite modified lithium metal battery negative electrode current collector as well as preparation method and application thereof
CN115566199A
Preparation method of two-phase proportion-adjustable high-entropy positive electrode material sodium ion battery
CN116207359A
Pomegranate-like high-entropy alloy / carbon nano hybrid material as well as preparation method and application thereof
CN116356369A
